Transformations in Māori Women's Identity: Some Things Change, Some Stay the Same - Houkamau, Carla Anne (Qualitative Research in Psychology, 2011)
While Māori (the indigenous people of New Zealand) retain a strong collective identity, cultural heterogeneity renders traditional conceptualisations of Māori identity increasingly problematic. To demonstrate the diverse ways Māori define and express their own identities, this article reports research that uses life-story interviews to explore personal perceptions of identity among 35 Māori women ages 18–75. Content analysis revealed traditional cultural factors (particularly whānau/family commitment) were important for identity among all participants, although the expression of these factors differed along with age and background. Older women raised in rural communities expressed family commitment through participating in social and economic activities within their own tribal networks. Younger, urbanised Māori expressed their identities by choosing careers which advanced Māori interests, supporting Māori political aspirations, and forming close relationships with other urban Māori. Life-story excerpts are used to illustrate distinct intergenerational differences in expressions of Māori identity as well as descriptions of “Māoriness,” seldom articulated in literature on the topic. The need to expand current paradigms of Māori identity to incorporate the diversity of group members is emphasised.
Keywords: colonisation; ethnic identity; kaumātua; mana wāhine; māori identity; urbanisation

Panguru and the city: kāinga tahi, kāinga rua : an urban migration history - Williams, Melissa Matutina (Bridget Williams Books, 2015)
Keywords: history; social conditions; social networks; te rarawa; urbanisation

Tradition and change in Maori leadership - Walker, Ranginui (Research Unit for Maori Education, University of Auckland, 1993)
Keywords: capitalism; colonisation; government; government relations; imperialism; kīngitanga; land loss; land theft; leadership; mana whenua; māori battalion; rangatira; urbanisation

Māori Urban Protest Movements - Taonui, Rawiri (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"--Publisher's information.
Keywords: discrimination; foreshore and seabed act 2004; government relations; hikoi ki waitangi; history; kaitiakitanga; land march; māori womens welfare league; nga tamatoa; parihaka; poverty; protest; racism; rangatiratanga; resistance; social conditions; springbok tour protests; takaparawhau bastion point; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; tāngata whenua; urbanisation

Mana Maori Motuhake: Maori Self-Determination - Levine, Hal; Henare, Manuka (Pacific Viewpoint, 1994)
Keywords: elections; he whakaputanga; land loss; mana motuhake; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; urbanisation; waitangi tribunal

The practice of tribalism in postcolonial New Zealand - Sullivan, Ann (Cultural Studies, 1995)
Keywords: post-colonialism; tikanga | indigenous law; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; urbanisation

“Maori sovereignty” Donna Awatere 1982 - Kamau, Laura-Margaret Ngahere Te Pohe (2010)
This thesis explores the ambivalent nature of Maori political theory as expressed through the writings of Donna Awatere in her publication Maori Sovereignty. Consequently it traces the intellectual history of Maori political thought with a particular emphasis on how Maori have traditionally perceived and advanced their ‘sovereignty’ and its equivalent term, ‘tino rangatiratanga’. The reason for this emphasis is to show how Awatere changed Maori perception of their tino rangatiratanga when she coined the phrase ‘Maori Sovereignty’ in 1982. This work offers an insider’s account into New Zealand’s ‘movements of unity’ that had occurred during the 1970’s and 1980’s based on Awatere’s personal experiences and involvement in various groups. Further it sets out to capture the influences and events that led Awatere to write Maori Sovereignty in order to demonstrate how she had advanced Maori understanding of their tino rangatiratanga. In addition, its attempts to broaden Maori understanding of their tino rangatiratanga by analysing Awatere’s political theory in juxtaposition with global trends, more specifically, the decolonisation and nationalistic processes that occurred in the decades following World War Two. This thesis argues that Maori Sovereignty differed greatly from any other work previously written by both Maori and Pakeha as it challenged existing interpretations of how Maori had perceived and had advanced their tino rangatiratanga. Subsequently, Maori Sovereignty has carved its place as one of New Zealand’s most debated and misunderstood publication to ever come out of the 1980’s and because of this, the lack of proper analysis has given cause for this thesis.
Keywords: activism; decolonisation; land; land return; tino rangatiratanga; urbanisation

Identity and socio-historical context : transformations and change among Māori women [Doctoral dissertation, University of Auckland] - Houkamau, Carla (2023)
ABSTRACT Several writers have argued that New Zealand’s colonial history has thwarted optimal identity development among Māori (Awatere, 1984; Lawson Te-Aho, 1998a; 1998b). In recent decades the view that Māori identity may be restored via enculturation has gained widespread acceptance (Broughton, 1993; Edwards, 1999). Recent research indicates, however, that many Māori perceive their identities in ways that differ from the enculturated ideal (Borrell, 2005; Te Hoe Nuku Roa, 1996; 1999). Relatively little is known of the diverse interpretations that comprise ‘alternative’ Māori identity forms. This thesis aims to contribute to current understandings of Māori identity by exploring identity change across three generations of Māori women. For the purposes of the research, identity was treated as ‘held’ within personal life-stories and transformations were investigated by comparing the life-stories of 35 Māori women from different age groups. Attention was given to the impact of three socio-historical processes on identity: the mass migration of Māori from rural to urban locations after the 1950s, the drive towards Māori assimilation which underpinned Government policy towards Māori until the late 1960s, and the Māori political and cultural renaissance which gathered momentum in New Zealand from the 1970s. Data analyses found participants born prior to urbanisation evaluated their Māori identities positively and this seemed to reflect their isolation from Pākehā and exposure to competent Māori role models during their formative years. Participants aged between 35 and 49 expressed disharmony and tension around their Māori identities which many attributed to their early exposure to negative evaluations of Māori people. ‘Post-renaissance’ Māori, aged between 18 and 35, reported prizing their cultural distinctiveness from a young age and affirmed Māori political, cultural and social equality despite what they perceived as enduring Pākehā prejudice. This interpretation appeared to reflect their early exposure to educational experiences which imparted a sense of cultural pride and a national news media which publicised Māori political activism. Women’s life-stories reveal distinct intergenerational differences, a multiplicity of interpretations of Māori identity not widely articulated in literature, and the need to expand current paradigms of Māori identity to incorporate the individuality of group members.
Keywords: crown policy; identity; urbanisation; wāhine māori

A Māori perspective of being and belonging - Rameka, Lesley (Contemporary Issues in Early Childhood, 2018)
Belonging and being are inextricably linked. From a M?ori perspective, belonging and being can be viewed through a number of interconnected historical and contemporary frames. One frame is derived from M?ori perceptions of the creation of the universe and genealogical relationships to the universe and everything in it. Another frame of belonging and being stresses increasingly diverse and complex positionings that require negotiation of radically different terrains of assumptions, behaviours, values and beliefs. This article explores two interrelated aspects of being and belonging from a M?ori perspective: whakapapa (?genealogical connections?) and whanaungatanga (?family relationships?). It discusses how each aspect has changed over time as a result of colonisation, urbanisation and western education, and identifies how the reflection of each has been transformed.
Keywords: belonging; colonisation; education; urbanisation; whakapapa; whanaungatanga

Concurrent Narratives of Maori and Integration in the 1950s and 60s - Harris, Aroha (Journal of New Zealand Studies, 2008)
Maori and government policies of integration in the 1950s and 60s by accessing two concurrent narratives are discussed. The two narratives are the narrative of the state embedded in a one-size-fits-all Maori policy, and the narratives of the Maori 'business of life'.
Keywords: crown policy; social conditions; urbanisation

Letty Brown, Wahine Toa - Harris, Aroha (Shifting Centres: Women and migration in New Zealand history, 2002)
History of Lettty Brown, advocate and member of groups such as the Womens Welfare League during urbanisation 1950s-1906s
Keywords: mana wāhine; urbanisation

The Structure of Urban Māori Identities - Kukutai, Tahu (Indigenous in the City: Contemporary Identities and Cultural Innovation, 2013)
Research on Indigenous issues rarely focuses on life in major metropolitan centres. Instead, there is a tendency to frame rural locations as emblematic of authentic or "real" Indigeneity. While such a perspective may support Indigenous struggles for territory and recognition, it fails to account for large swaths of contemporary Indigenous realities, including the increased presence of Indigenous people in cities. The contributors to this volume explore the implications of urbanization on the production of distinctive Indigenous identities in Canada, the US, New Zealand, and Australia. In doing so, they demonstrate the resilience, creativity, and complexity of the urban Indigenous presence.
Keywords: identity; urbanisation